Co-gasification of sub-bituminous coal with palm kernel shell in fluidized bed coupled to a ceramic industry process. (25th August 2016) - Valdés, Carlos F.; Chejne, Farid; Marrugo, Gloria; Macias, Robert J.; Gómez, Carlos A.; Montoya, Jorge I.; Londoño, Carlos A.; De La Cruz, Javier; Arenas, Erika
Highlights: Implementation of co-gasification in a reactor PKS-SubbA coal (10/90) mixture. Co-gasification resolved some problems of flow pattern anomalies in biomass in LF. Substitution efficiently of the traditional use of pulverized coal in tunnel kiln. Production of syngas suitable for a brick baking process. Innovative development and coupling of co-gasification to industrial process. Abstract: This paper presents the results of co-gasification of Sub-bituminous coal type A (SubbA coal) with palm kernel shell (PKS) in a fluidized bed gasifier to meet the energy requirements for baking 300 tons/day of bricks in a tunnel kiln. Standardized operation of the co-gasification process of the SubbA coal – PKS 90/10 wt.% mixture was confirmed for a 24 h run. The reactor has the capacity to process up to 700 kg/h of the mixture, using air and an air/steam as the gasifying agent at 800°C, with an equivalent ratio of air/fuel (ER) between 0.5 and 0.7 and a steam/fuel ratio of 0.2. The product syngas had a HHV of 5.0 MJ/Nm 3 that efficiently substitutes and the traditional use of pulverized coal by means of carbojets into the tunnel kiln without affecting the production process, while using a much cleaner gas to cook the bricks with lower emissions. This demonstrating the synergy existing in this coupling. Positive results of these experiments can enhance figure use of coal in a clean manner. This technology is mature enough to be implemented as a continuous energy supply to industrial processes that currently use traditional combustion for heat.